Where does all this waste come from?. Issue 8 (26th June 2015) - Raschke, Wolfgang; Zilli, Massimiliano; Loinig, Johannes; Weiss, Reinhold; Steger, Christian; Kreiner, Christian; Biró, Miklós; Messnarz, Richard; Colomo‐Palacios, Ricardo
Abstract Agile development processes are more flexible than conventional ones. They emphasize iterative development and learning over feedback loops. Nevertheless, we experienced some pitfalls in the application of agile processes in dependable software systems. We present here the experiences we gathered in the construction of high‐quality industrial software. Moreover, we will digest our experiences into a conceptual model of waste creation. This model will be refined to a case study where we take appropriate measurements in order to provide empirical evidence for it. Finally, we discuss the implications of the developed model, which helps to estimate the trade‐off between agile and traditional software processes. Copyright © 2015 John Wiley & Sons, Ltd.